106k views
4 votes
Factor x3 – 7x2 – 5x + 35 by grouping. What is the resulting expression?

2 Answers

6 votes

Answer:


x^3 - 7x^2 - 5x + 35=(x-7)(x-√(5))(x+√(5))

Explanation:

We are given a expression:


x^3 - 7x^2 - 5x + 35


x^3 - 7x^2 - 5x + 35\\\\=x^2(x-7)-5(x-7)\\\\=(x^2-5)(x-7)

We know that
a^2-b^2=(a-b)(a+b)

So,
x^2-5=x^2-(√(5))^2 \\\\=(x-√(5))(x+√(5))

So,
x^3 - 7x^2 - 5x + 35=(x-7)(x-√(5))(x+√(5))

User Chansik Im
by
5.3k points
4 votes

Answer:


(x-7)(x-√(5))(x+√(5))

Explanation:

The given expression is


x^3-7x^2-5x+35

Factor the first two and the last two.


x^2(x-7)-5(x-7)


(x-7)(x^2-5)

Apply difference of two squares to the leftmost factor.


(x-7)(x-√(5))(x+√(5))

User Tom Geoco
by
5.3k points